Consumer behavior in tourism and hospitality research - Woodside, Arch G.; Decrop, Alain (Emerald Publishing Limited, 2017)
This portrait of contemporary tourists proposes that these travelers create consumption audio-portraits and self-explanations (identity constructions) through their purchases and use of travel-related services. Their configurations of destinations, accommodations, travel modes, in-route and destination activities, meal choices, sites/attractions visited, and their travel companions inform others and themselves about who they are. These understandings of self through travel are statements of being - where I've been and what I've done tells me and others who I am. Also, one's definition of self (being) affects tourists' future configurations of travel-related buying and consumption. Thus, tourism-related behavior and being represent virtuous and sometimes vicious consumption systems. Consequently, most tourists are identifiable by who they are and what they know about where they have been and what they have done via their summaries of their trips. The chapters in this volume provide tools and evidence useful for deep understanding of tourists' buying, consumption, and being through examinations of consumer's self-descriptions of personal markers of their trip configurations. This volume's core tenet is that thick descriptions and case-based models are essential steps for highly useful research and deep understanding of tourism behavior. - Resumé vydavatel
Obsahuje index.
Keywords: spotřebitelské chování; cestovní ruch; pohostinství; consumer behavior; tourism; catering trade; kolektivní monografie; elektronické knihy; collective monographs; electronic books